Visual language approach to representing KBimCode-based Korea building code sentences for automated rule checking. Issue 2 (20th August 2018) - Kim, Hayan; Lee, Jin-Kook; Shin, Jaeyoung; Choi, Jungsik
Graphical abstract: Abstract: The Building Information Modeling (BIM) and its applications enable an automatic building permit process based on 3D building models and their associated information. A crucial part of the building permit process is the interpretation and transformation of natural language-based building regulation into a computer-readable and executable format. As other countries and their projects have developed a certain type of rule-translation methods, KBimCode, part of the KBim application series, has been developed and supported by the Korean government to ignite an automatic, BIM-based building permit system on top of the current e-submission system, which is called Seumter. The rule translation process usually employs a computer hard-coded approach because of its ease of implementation, and there have been advances in making the computer understand the natural language-based building regulations using parametric input tables and script languages. This project includes a step for developing a logic rule-based approach for translating natural language into computer-executable code. However, the main contribution of this study is the introduction of an approach to represent such text-based regulations using visual language for novice programmers, architects, and rule reviewers. This paper describes a KBimCode visual language that is easy-to-write and intuitive because it uses visual symbols instead of textual coding.